2002
DOI: 10.1002/j.2168-9830.2002.tb00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Web‐Based Readiness Assessment Quizzes

Abstract: Student readiness to fully participate in designed educational activities is often impeded by a lack of individual preparation through assigned readings or study. However, student preparation is rarely treated as an integral part of course design. Consequently, webbased readiness assessment quizzes were developed for three courses in biological/biosystems engineering, at the freshman and junior levels. The overall goal was to improve student preparatory reading by assessing lower-level knowledge just prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…While the primary focus of Web-based delivery has been in the development of standalone Web-based distance education courses, more faculty members are beginning to use the Web to supplement and enhance on-campus instruction (e.g., Goldberg, 1997;Henson, Fridley, Pollock, & Brahler, 2002;Marks, 2002; Masten, Chen, Graulau, Kari, & Lee, 2002; Mohtar & Engel, 2000;Patterson, 1999;Stith, 2000;Wallace & Weiner, 1998). Data collected by The Campus Computing Project (1999) revealed that 28% of higher education courses have an associated Web page compared to 9% in 1996.…”
Section: Introductionmentioning
confidence: 99%
“…While the primary focus of Web-based delivery has been in the development of standalone Web-based distance education courses, more faculty members are beginning to use the Web to supplement and enhance on-campus instruction (e.g., Goldberg, 1997;Henson, Fridley, Pollock, & Brahler, 2002;Marks, 2002; Masten, Chen, Graulau, Kari, & Lee, 2002; Mohtar & Engel, 2000;Patterson, 1999;Stith, 2000;Wallace & Weiner, 1998). Data collected by The Campus Computing Project (1999) revealed that 28% of higher education courses have an associated Web page compared to 9% in 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The use of laptops in the classroom did not have a statistically significant impact on student scores 36 . Page 14.592.7 Students were more likely to read course materials to prepare for an online readiness assessment quiz 40 . A separate study 37 showed that students were more comfortable working on technical problems with no clear answers.…”
Section: Surveymentioning
confidence: 99%
“…In the 2005/06 and 2006/07 academic years, students in the course were evaluated based on five components (as summarized in Table 1): two technical writing articles (20%), one computer Page 13.494.3 assignment (10%), one midterm examination (20%), 15 in-lecture Readiness Assessments Tests 7,8 (10%), and two design projects (40%). This year, the students will be evaluated based on two written assignments (10%), a midterm, in-lecture quizzes (10%), and the design project including interim work, presentation, and final report (20%).…”
Section: Course Modelmentioning
confidence: 99%
“…It is difficult to teach students if they are not there. For about sixty percent of the lectures, Readiness Assessment Tests 7,8 (RAT) were used to ensure students completed an assigned reading and attended class. Most of the in-class quizzes had three multiple-choice questions.…”
Section: Course Modelmentioning
confidence: 99%